PENGARUH PENGALAMAN DAN KEPERCAYAAN TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN (Studi Kasus pada H&M DKI Jakarta) - Mirari Yovanda (2022)
This research uses descriptive quantitative method with software analysis tool SmartPLS 3.0. And the distribution technique is done by survey using google form. The purpose of this study was to determine the effect of Experience and trust on loyalty through intervening variables of customer satisfaction H&M DKI Jakarta. Using the sample method, namely purposive sampling with a total sample of 100 responsdents. The criteria taken are consumers who have shopped at least 2 times. The results show (1) the Experience variable has no significant effect on loyalty; (2) the trust variable has no significant effect on loyalty; (3) the Experience variable has a significant effect on loyalty through satisfaction; (4) the trust variable has a significant effect on loyalty through satisfaction.